2012
DOI: 10.1111/j.1551-2916.2012.05273.x
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum and Neodymium Solubility in Simplified SiO2B2O3Na2OAl2O3CaO High Level Waste Glass

Abstract: Lanthanum and neodymium incorporation in simplified high level waste glasses has been investigated for SiO 2– B 2 O 3– Na 2 O – Al 2 O 3– CaO compositions quenched from 1200°C, for varying La /( La  +  Nd ) (atomic) and increasing rare‐earth oxides contents. In this system and beyond the solubility limit, rare‐earths (RE) elements are reported to form apatite phases with the general formula Ca 2 RE 8( SiO 4)6 O 2. In the current study, speciation of these trivalent RE 3+ cations in both amorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…X-ray diffraction (XRD) data was collected on an X' Pert PRO diffractometer using Cu-K α radiation (λ=1.54187 Å) [31,32]. For XRD measurement, powdered samples with particle size80 μm were used.…”
Section: Methodsmentioning
confidence: 99%
“…X-ray diffraction (XRD) data was collected on an X' Pert PRO diffractometer using Cu-K α radiation (λ=1.54187 Å) [31,32]. For XRD measurement, powdered samples with particle size80 μm were used.…”
Section: Methodsmentioning
confidence: 99%
“…In complicated starting glass compositions, energy dispersive spectroscopy (EDS) has shown that multiple RE cations, for example, Y 3+ , La 3+ , Ce 3+ /Ce 4+ , Pr 3+ , Nd 3+ , Sm 3+ , along with alkali (for example, Na + ), and alkaline earth ions (for example, Ca 2+ , Sr 2+ ) can simultaneously incorporate into the oxyapatite structure [5]. In comparing La, Nd, and La+Nd in Na-Ca aluminoborosilicate glasses, it was observed that the amount of RE 2 O 3 that could be accommodated in the glass before apatite crystallization was higher for La than Nd, and that overall apatite composition depended on the RE cation present [36].…”
Section: Most Studies Of Oxyapatite Crystallization In Nuclear Waste mentioning
confidence: 99%
“…¼ ði=ZrÞ altered glass ði=ZrÞ pristine glass (6) A ratio C(i)/C g < 1 in the altered glass means that the altered glass was depleted in element i compared with the pristine glass, whereas a ratio C(i)/C g > 1 indicates that the altered glass was enriched in element i. The transition between the altered glass and the pristine glass was defined as corresponding to a C(i)/C g ratio of 0.5.…”
Section: Cðiþ C Gmentioning
confidence: 99%
“…4 Glasses with high rare earth (RE) contents are particularly interesting since REs form a substantial proportion of the waste and are commonly used as non-radioactive surrogates for actinides. [5][6][7] Two composition ranges, both in the SiO 2 -B 2 O 3 -Al 2 O 3 -Na 2 O-CaO-RE 2 O 3 system, have already been explored. [8][9][10][11][12][13][14][15][16] These two domains of composition are defined by the molar oxides R ) with M and M' corresponding to alkaline and alkalineearth elements, respectively.…”
Section: Introductionmentioning
confidence: 99%